Neoadjuvant Interdigitated Chemoradiotherapy Using Mesna, Doxorubicin, and Ifosfamide for Large, High-grade, Soft Tissue Sarcomas of the Extremity: Improved Efficacy and Reduced Toxicity. (January 2019) - Chowdhary, Mudit; Sen, Neilayan; Jeans, Elizabeth B.; Miller, Luke; Batus, Marta; Gitelis, Steven; Wang, Dian; Abrams, Ross A.
Abstract : Objectives: Patients with large, high-grade extremity soft tissue sarcoma (STS) are at high risk for both local and distant recurrence. RTOG 95-14, using a regimen of neoadjuvant interdigitated chemoradiotherapy with mesna, doxorubicin, ifosfamide, and dacarbazine followed by surgery and 3 cycles of adjuvant mesna, doxorubicin, ifosfamide, and dacarbazine, demonstrated high rates of disease control at the cost of significant toxicity (83% grade 4, 5% grade 5). As such, this regimen has not been widely adopted. Herein, we report our institutional outcomes utilizing a modified interdigitated chemoradiotherapy regimen, without dacarbazine, and current radiotherapy planning and delivery techniques for high-risk STS. Materials and Methods: Adults with large (≥5 cm; median, 12.9 cm), grade 3 extremity STS who were prospectively treated as part of our institutional standard of care from 2008 to 2016 are included. Neoadjuvant chemoradiotherapy consisted of 3 cycles of mesna, doxorubicin, and ifosfamide (MAI) and 44 Gy (22 Gy in 11 fractions between cycles of MAI) after which patients underwent surgical resection and received 3 additional cycles of MAI. Results: Twenty-six patients received the MAI treatment protocol. At a median follow-up of 47.3 months, 23 (88.5%) patients are still alive. Three year locoregional recurrence-free survival, disease-free survival, and overall survival are 95.0%, 64.0%, and 95.0%, respectively. There have been no therapy-related deaths or secondary malignancies. The nonhematologic grade 4 toxicity rate was 7.7%. Conclusions: Neoadjuvant interdigitated MAI radiotherapy followed by resection and 3 cycles of adjuvant MAI has resulted in acceptable and manageable toxicity and highly favorable survival in patients at greatest risk for treatment failure.